THE CHALLENGES AND OPPORTUNITIES EXPERIENCED BY SPORTS TRACK STUDENTS DURING THE COVID-19 PANDEMIC - Layao, Michelle Mordeno (Universitas Pendidikan Indonesia, 2023)
The COVID-19 pandemic has greatly affected the way people think, feel, and do things. In the Philippines, the whole nation experienced the “new normal” ways, such as on the context of education. The Mindanao State University System (MSUS), particularly, created Flexible Learning Options where lectures may be done either: (a) synchronous event where online live lectures through streaming is applied using video conferencing platforms such as Zoom or Google Meet, or (b) asynchronous event where online lecture is prepared using screen recorder apps. Course books and modules were also prepared to be used by the students. The MSU-Marawi Senior High School followed these guidelines in the delivery of teaching-learning experiences. In this study, the problems/challenges, opportunities, and recommendations associated with the delivery of lessons specifically experienced by the Sports Track students were investigated. Based on their first-hand experiences, recommendations straight from the students were also listed. Information such as age, sex, grade level, current location, family monthly income, gadgets used, connectivity used, and average monthly expenses on connectivity were also taken. It was found out that students experienced: (1) Difficulties acclimating to new learning methods and demands, (2) Poor/insufficient internet connection, and (3) Financial constraints. However, because of the pandemic, they were able to have: (1) More family time and bonding, and (2) Self-discovery and self-motivation to learn. They then made recommendations such as: (1) Free internet connectivity and improved internet speed, (2) Sponsored gadgets, (3) Resumption of face-to-face classes, and (4) Consultation and consideration from teachers. Keywords: problems/challenges, opportunities, recommendations, MSU-MSHS Sports Track students, COVID-19 pandemic